FACTORS – FORMING SHOPPING CONSUMER PREFERENCES IN TRADITIONAL MARKET - Nanda Hafiz Pratama Lubis (Teknik Informatika Universitas Malikussaleh, 2019)
Traditional markets are built and managed by the Government, Private Sector, Cooperatives or non-governmental organizations as business facilities or places in the form of shops, kiosks, kiosks, tents owned / managed by small and medium traders and cooperatives, small capital and small-scale businesses where the sale and purchase process occurs through bargaining. This study aims to find factors forming consumer preferences for shopping at Traditional Markets. The research method in this study uses quantitative methods. The population and sample in this study were people who shop in traditional markets with 95 people each in the traditional markets studied. This study uses questionnaire techniques and documentation. From the literature study and previous studies compiled the preference factors that become hypotheses, namely accessibility, price, completeness of goods and transportation. The results of hypothesis testing in three markets in the city of Medan showed that the factors that could most influence consumers' preferences for shopping in traditional markets were the price factor (3,942). From the discussion it can be concluded that the price factor is very dominant in determining people's shopping preferences. For example, although accessibility is not good and the goods are complete, consumers still come shopping in the market. The price factor is strongly influenced by economic conditions (Makori 2015) and is not directly related to the physical conditions of the market such as accessibility and transportation. The author suggests that traditional markets need to be conditioned so that prices remain cheaper so that people continue to shop in traditional markets, without seeing good facilities and market accessibility.